The Effect of Hedonic Motivation and Twin Date Promos on Impulse Buying Mediated by FOMO - Mardia Mardia; A. Zuliansyah; Nurhayati Nurhayati (Dinasti Review, 2026)
This study examines the influence of hedonic shopping motivation and twin date promo events on impulse buying, with Fear of Missing Out (FOMO) as a mediating variable, among Generation Z Shopee users in Bandar Lampung. A quantitative survey method was employed with 100 respondents selected via purposive sampling. Data were analyzed using SEM-PLS with SmartPLS 4. Results show that: (1) hedonic shopping motivation has a positive and significant direct effect on impulse buying; (2) twin date promo events have a positive and significant direct effect on impulse buying; (3) FOMO significantly mediates the effect of hedonic motivation on impulse buying; and (4) FOMO significantly mediates the effect of twin date promo events on impulse buying. From an Islamic business perspective, this behavior risks transgressing the prohibitions on israf (extravagance) and tabdzir (waste), underscoring the need to apply the principles of al-iqtisad (moderation) and maslahah (genuine benefit) in every consumption decision.